2013
DOI: 10.1038/labinvest.2013.65
|View full text |Cite
|
Sign up to set email alerts
|

An endovascular canine stroke model: middle cerebral artery occlusion with autologous clots followed by ipsilateral internal carotid artery blockade

Abstract: Stroke is one of the leading causes of death worldwide and the main reason for long-term disability. An appropriate animal model of stroke is urgently required for understanding the exact pathophysiological mechanism of stroke and testing any new therapeutic regimen. Our work aimed to establish a canine stroke model occluding the middle cerebral artery (MCA) and blocking the ipsilateral internal carotid artery (ICA), and to assess the infarct lesions by magnetic resonance imaging. The stroke model was generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Jahan et al 29 did not evaluate whether the procedure results in ischemia, but they used this model to demonstrate pharmacological thrombolysis using plasmin delivered intraarterially. In dogs with much larger arteries there is more flexibility in navigating catheter and two routes for occluding canine MCA were reported with approach via internal carotid artery 32 or via vertebral artery (VA) 33 . Stroke volume in dogs with ICA emboli injection varies depending on clot size and was the largest in group with clot 1.4 mm/1.7 mm combined with additional ipsilateral ICA transient occlusion (4173.23 ± 603.22 mm 3 ) 14,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Jahan et al 29 did not evaluate whether the procedure results in ischemia, but they used this model to demonstrate pharmacological thrombolysis using plasmin delivered intraarterially. In dogs with much larger arteries there is more flexibility in navigating catheter and two routes for occluding canine MCA were reported with approach via internal carotid artery 32 or via vertebral artery (VA) 33 . Stroke volume in dogs with ICA emboli injection varies depending on clot size and was the largest in group with clot 1.4 mm/1.7 mm combined with additional ipsilateral ICA transient occlusion (4173.23 ± 603.22 mm 3 ) 14,32 .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 male beagles (13–15 kg; Laboratory Animal Center of Nanjing Medical University) were anesthetized by intravenous injection with 3 ml/kg pentobarbital (Pentobarbital Sodium Salt; Chemical Reagent Company, Shanghai, China). Detailed procedures were described in our previous studies ( 18 20 ). In brief, two autologous clots (1.4 and 1.7 mm in diameter and 5 mm in length) were injected into the left middle cerebral artery (MCA).…”
Section: Methodsmentioning
confidence: 99%
“…The aim of the present study was to evaluate the temporal evolution of rDWI and rADC in three different b values, and further compare their diagnostic performances in identifying the onset time of acute ischemic stroke, based on an embolic canine model with clear onset time ( 18 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Clinical rating scores and neurological assessment scores of large animal research models have been reported for gene therapy in feline models of the GM1 and GM2 gangliosidoses, 13,14 canine models of Duschenne muscular dystrophy, 15 and in rabbit and canine stroke models. [16][17][18] In the current project, we hypothesize that the neurological assessment score developed for the XLMTM dog model correlates with genotype and established measures of disease severity, such as hindlimb strength. We also hypothesize that scoring is reliable when performed by an independent observer.…”
Section: Introductionmentioning
confidence: 97%